UTAUT2 Approach to Byond BSI Adoption in Padang: Mediation and Moderation Effects - Nurul Mu'tamim; Vidyarini Dwita (INOVTEK Polbeng - Seri Informatika, 2025)
The use of Islamic mobile banking apps is still not optimal, even though people’s interest in digital finance is growing. This study examines how social influence, enjoyment (hedonic motivation), and user habits shape people’s intention to use these apps and how that intention affects actual usage. It also tests whether word of mouth (WOM) strengthens the link between intention and behavior. Using a quantitative approach, the study surveyed 105 active BYOND BSI users in Padang City through purposive sampling. Data were analyzed with the PLS-SEM method using SmartPLS 4.0 and bootstrapping with 5,000 samples to ensure reliable results. The findings show that enjoyment and habit strongly affect intention, and intention significantly impacts actual use. However, social influence has no significant effect on intention, and WOM does not moderate the relationship between intention and use. Moreover, intention mediates the effects of enjoyment and habit on use but not that of social influence. Overall, the results highlight that users’ positive experiences and consistent habits are key drivers behind their intention and actual use of Islamic mobile banking services.